Study of the \(^nat\)Sm\((γ ,xn)^143m,g\)Sm Reactions Induced by Bremsstrahlung with End-point Energies Just above GDR Region - Khue, Pham Duc; Do, Nguyen Van (Communications in Physics, 2014)
We investigate the energy dependence of the isomeric yield ratios for the \(^nat\)Sm\((γ ,xn)^143m,g\)Sm reactions with bremsstrahlung energies of 40-, 45-, and 50-MeV, just above the giant dipole resonance (GDR) region by the off-line γ -ray spectrometric method. The bremsstrahlung photons were produced from the 100 MeV electron linear accelerator (linac) at the Pohang accelerator laboratory (PAL), Pohang, Korea. In order to improve the accuracy of the experimental results the necessary corrections were made. The present results are compared with similar literature data of the ^natSm(γ ,xn)^143m,gSm reactions measured at various photon energies and of the ^natSm(n,2n)^143m,gSm reaction induced by 14 MeV neutrons in order to examine the effects of an excitation energy and an input angular momentum.